The Mediating Role of Work Flow in The Relationship Between Need Satisfaction and Subjective Well-Being - Hakan Sarıyıldız; Sergen Sırmacı; Fatma Aksoy; Pelin Bintaş Zörer (Yaşam Becerileri Psikoloji Dergisi)
Work life, as a significant part of adulthood, interacts with individuals' basic psychological needs and subjective well-being. This study examines the mediating role of work-related flow experiences in the relationship between the satisfaction of basic work-related needs and subjective well-being. Planned as a cross-sectional survey study, this research reached 183 participants over the age of 18 and actively employed, through online data collection in line with the stated purpose. We utilized the Demographic Information Form, the Work-Related Basic Need Satisfaction Scale, Satisfaction With Life Scale, Positive and Negative Affect Schedule (The PANAS Scale) and The Work-Related Flow Inventory as measurement tools. Correlation, regression, and Hayes Process Macro mediation analyses revealed that competence, autonomy, and relatedness—fundamental psychological needs in the workplace—were positively and significantly associated with both work flow and subjective well-being. As a result of the correlation, regression, and Hayes Process Macro mediation analyses, it was found that the basic work-related needs of competence, autonomy, and relatedness were in a positive and significant relationship with work flow and subjective well-being; that the satisfaction of these needs and the flow experience at work explained 38% of subjective well-being; that psychological need satisfaction and work flow experience positively and significantly predicted subjective well-being; and that work flow experience played a mediating role in this relationship. As a result, the findings of the study show that since the work flow experience mediates the relationship between the satisfaction of psychological needs and subjective well-being, especially employers, by enabling their employees to make decisions freely, can support the need for autonomy, by allowing them to engage in trust-based interactions with other employees in the workplace, can support the need for relatedness, and by helping them feel competent in relation to the tasks in the work environment, can support the need for competence, and thus may contribute to employees’ subjective well-being.